1984
DOI: 10.1007/bf00185128
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of natural and non-crustal ferrimagnetic minerals in soil-sized particulates from the Mediterranean atmosphere

Abstract: Magnetic susceptibility (Z) values have been measured in 38 soil-sized atmospheric particulates from the Mediterranean Sea and surrounding regions, and have been used to assess the factors which control the distribution of ferrimagnetic minerals in the Mediterranean aerosol. Soil-sized components generated from the North African desert belt have Z values in the range ~25 to ~65 1 0 -6 G Oe -l c m -3 g -I , whereas those originating in deserts lying to the east of the Mediterranean have higher values which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…Our data on magnetic parameters provided evidence on the atmospheric versus riverine input of particles and some strong indications about the presence of anthropogenic particles in offshore deep-sea sediments in this region. Moreover, the data indicated that Saharan dust and anthropogenic particles coexisted in the sediments, supporting the hypothesis that Saharan dust episodes could play an important role in facilitating deposition and co-precipitation of anthropogenic particles from the atmosphere and the water column [56,67]. …”
Section: The Gulf Of Lionssupporting
confidence: 57%
See 1 more Smart Citation
“…Our data on magnetic parameters provided evidence on the atmospheric versus riverine input of particles and some strong indications about the presence of anthropogenic particles in offshore deep-sea sediments in this region. Moreover, the data indicated that Saharan dust and anthropogenic particles coexisted in the sediments, supporting the hypothesis that Saharan dust episodes could play an important role in facilitating deposition and co-precipitation of anthropogenic particles from the atmosphere and the water column [56,67]. …”
Section: The Gulf Of Lionssupporting
confidence: 57%
“…The purpose of the study was to test the capabilities of the magnetic methodology in tracing the dispersion of contaminants in the marine environment. Previous works [53,56] have shown that particles originating from fossil fuel combustion exhibit strong ferrimagnetic behavior and correspond to coarse magnetic grains. Our task was to decipher their presence in marine sediments [57].…”
Section: The Gulf Of Lionsmentioning
confidence: 97%
“…The only published rock magnetic data for Eastern Mediterranean regional dust samples which we are aware are magnetic susceptibility data from atmospheric particulates collected in 0.5-µm nylon meshes on board scientific cruises (Chester et al, 1984). Although no grain size data were reported for these dust samples, they are expected to have a modal grain size similar to that of regional NES dust collected at Crete (8-30 µm, Mattsson and Nihlén, 1996) and Israel (20-40 µm, Yaalon and Ganor, 1979).…”
Section: Dustmentioning
confidence: 99%
“…Outbreaks of dust-laden Saharan air over the Mediterranean and southern Europe are quite frequent (Eriksson, 1979;Prodi and Fea, 1979;Ganor and Mamane, 1981;Bucher, 1986Bucher, , 1989Bucher and Lucas, 1984;Bucher et al, 1983; Loye-Pilot et al, 1986; Bergametti et al, 1989), and episodes of dust haze over Crete usually occur several times each year (Rapp and Nihlen, 1984;Nihlen and Solyom, 1989;Nihlen and Mattson, 1989). Saharan dust has been observed in Alpine snow (Haeberli, 1978;Wagenbach and Geis, 1989), and has been collected from the atmosphere over the Mediterranean (Tomasi et al, 1979;Prodi et al, 1983;Chester et at., 1977Chester et at., , 1984aChester et at., , 1984bTomadin et al, 1984). A significant Saharan dust component has also been identified in Quaternary marine sediments in parts of the Mediterranean (Venkatathnam and Ryan, 1971;Tomadin, 1974;Eriksson, 1979;Mazzucotelli et al, 1986;Tomadin and Lenaz, 1989).…”
Section: Introductionmentioning
confidence: 97%